The Implementation of Creative Problem Solving Learning Model Based on Statistical Ball Props to Improve Student Creativity in Statistics - Isna Umi Arifah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2019)
Education can basically help humans to develop and improve their scientific knowledge, so they are able to deal with the changes that occur in their lives. In this study the researcher observed the class IX of Zainul Ulum Plus Middle School. The study aims to improve student creativity and completeness of students in learning statistical material with the Creative Learning Model Solving based on statistical ball props. The type of research used is classroom action research (CAR). The procedure used is a cycle model. Based on the results of the study, the level of creativity of students in the first cycle was 2.78, then in the second cycle the average level of creativity of students was 2.99 with the category of the level of creativity of good students. While the average student learning outcomes in the first cycle amounted to 77.16 with a percentage of classical completeness of 67% while in the second cycle obtained an average value of 92.75 with a percentage of 100% classical completeness. The average percentage of student learning activities in learning cycle I is 83% and in the second cycle is 86% with the category of good student learning activities. Keywoard: creative problem solving, statistic ball, student creativity